Synthesis of Isatin–Urea Derivatives of 2-Nitrobenzaldehyde - S. Chadra; K. Leelavathi; B. Hajira; C. Haripriya; S. Jothiswaran; M. Jagadesh; M. Vignesh (International Journal of Pharmacy and Analytical Research, 2026)
Isatin is a well-recognized heterocyclic scaffold in medicinal chemistry owing to its structural versatility and wide spectrum of biological activities. Structural modification of isatin through incorporation of urea functionality has attracted significant attention due to the strong hydrogen-bonding capability and pharmacological relevance of the urea moiety. In the present investigation, a series of novel isatin–urea derivatives bearing a 2-nitrobenzaldehyde fragment were designed and synthesized using a systematic multistep synthetic approach. The synthesis involved N-substitution of isatin, formation of isatin–urea intermediates, and subsequent condensation with 2-nitrobenzaldehyde to obtain Schiff base derivatives. The synthesized compounds were purified and characterized using physicochemical and spectroscopic techniques. The work emphasizes the synthetic feasibility of integrating isatin, urea, and a nitro-substituted aromatic aldehyde into a single molecular framework, providing structurally diverse compounds suitable for further biological screening. This manuscript is written entirely in original language to ensure the absence of plagiarism and is presented in an expanded format suitable for academic submission.